PERANCANGAN APLIKASI PENCARIAN RUTE TERPENDEK LOKASI ATM (ANJUNGAN TUNAI MANDIRI) DI KOTA SEMARANG DENGAN ALGORITMA GENETIKA BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract ATM (Automated Teller Machine) is one of the common facilities with the latest technology that allows people to conduct financial transactions. Currently, ATM machines have been scattered in various corners of the region, not least in the city of Semarang. A large number of ATMs in the city of Semarang with scattered location, sometimes making some people find it difficult to look for it. Therefore, the authors designed an ATM location-based search apps Android by applying LBS (Location Based Service). This application has the potential to facilitate the Android users in the city of Semarang to locate the current position, then from the current position, the user can find the nearest ATM desired. Development of a hybrid system using a mobile development on Android Smartphone using Apache Server 2.2.8, MySQL DBMS 5.0.51b, IDE Eclipse Galileo, and JavaScript as well as online data storage will provide easy of use features in use on Android. Application of the method Haversine the shortest ATM location search feature is also very useful in finding the shortest distance between the user and the location of ATMs. After testing, the application searches the location of the ATM has been going well and managed from the administrator or user. Based on test results kompatibilita, the application searches the shortest ATM locations in the city of Semarang can run on the Android operating system version 2.2 (Froyo). Keywords: ATM, Genetic Algorithm, PhoneGhape